Integrated Behavioral Intervention to Improve HIV/AIDS Treatment Adherence and Reduce HIV Transmission - Kalichman, Seth C. (American Public Health Association, 2011)
Objectives. We conducted a randomized clinical trial to test an integrated behavioral intervention designed to enhance using HIV treatment as prevention by improving medication adherence, reducing risks for other sexually transmitted infections, and minimizing risk compensation beliefs. Methods. Individuals living with HIV/AIDS (n = 436) participated in a randomized clinical trial testing an intensive behavioral intervention aimed at reducing HIV transmission risks compared with an attention control condition. We used unannounced pill counts to monitor antiretroviral therapy adherence and computerized interviews to measure risk behaviors. Results. The integrated transmission risk reduction intervention demonstrated increased antiretroviral therapy adherence and less unprotected intercourse with nonseroconcordant partners at 3- and 6-month follow-ups as well as fewer new sexually transmitted infections diagnosed over the 9-month follow-up period (adjusted odds ratio = 3.0; P < .05; 95% confidence interval = 1.01, 9.04). The integrated intervention also reduced behavioral risk compensation beliefs. Conclusions. A theory-based integrated behavioral intervention can improve HIV treatment adherence and reduce HIV transmission risks. HIV treatment as prevention should be bundled with behavioral interventions to maximize effectiveness.